A miR‐155‐dependent microRNA hierarchy in dendritic cell maturation and macrophage activation. Issue 4 (18th January 2014) - Dueck, Anne; Eichner, Alexander; Sixt, Michael; Meister, Gunter
Abstract : MicroRNAs (miRNAs) are small RNAs that play important regulatory roles in many cellular pathways. MiRNAs associate with members of the Argonaute protein family and bind to partially complementary sequences on mRNAs and induce translational repression or mRNA decay. Using deep sequencing and Northern blotting, we characterized miRNA expression in wild type and miR‐155‐deficient dendritic cells (DCs) and macrophages. Analysis of different stimuli (LPS, LDL, eLDL, oxLDL) reveals a direct influence of miR‐155 on the expression levels of other miRNAs. For example, miR‐455 is negatively regulated in miR‐155‐deficient cells possibly due to inhibition of the transcription factor C/EBPbeta by miR‐155. Based on our comprehensive data sets, we propose a model of hierarchical miRNA expression dominated by miR‐155 in DCs and macrophages. Abstract : Analysis of miRNA expression upon stimulation of macrophages and maturation of dendritic cells. miRNA expression analyses in wild type and miR‐155‐deficient cells. Identification of miRNAs that are affected by miR‐155. MiR‐455 is a potential target of C/EBPbeta, which is in turn directly regulated by miR‐155. Establishment of a miR‐155‐dependent miRNA hierarchy in macrophages and dendritic cells.